IMPLEMENTASI PEMIKIRAN THOMAS LICKONA TENTANG PENDIDIKAN KARAKTER DALAM MANAJEMEN PENDIDIKAN ISLAM - Abdul Mahruf; Widya Andriyani; Kholil Lur Rochman (STKIP Pesisir Selatan, 2026)
This study was motivated by the moral crisis in education, marked by an increase in cases of violence, bullying, and ethical degradation in schools. This situation highlights the need for education that emphasizes not only cognitive aspects but also character building in students. The purpose of this study is to analyze Thomas Lickona's thoughts on character education and examine its relevance for implementation in Islamic education management. This study was conducted qualitatively using library research. Data were obtained through library documentation, namely books, scientific journal articles, and relevant previous research results. Data analysis was conducted using descriptive qualitative techniques through the stages of data reduction, presentation, and conclusion drawing. The results of this study indicate that the three main components of character education according to Lickona are moral knowing, moral feeling, and moral action. All three are relevant to Islamic values such as piety, justice, and responsibility. The implementation of Lickona's ideas in Islamic education management can be done through value-based planning, exemplary teachers and leaders, the cultivation of a religious culture and local wisdom, and good administration.